Dogwood Borer, Synanthedon scitula (Harris) (Insecta: Lepidoptera: Sesiidae) - Jamba Gyeltshen; Amanda Hodges (EDIS)
EENY-374, a 4-page illustrated fact sheet by Jamba Gyeltshen and Amanda Hodges, describes this destructive pest of flowering dogwood and other cultivated trees. Part of the Featured Creatures series, this publication covers the distribution, description, biology, host plants, damage, management, and selected references. Part of the Featured Creatures Collection. Published by the UF Department of Entomology and Nematology, May 2006.